Implementasi E-Audit System Pada Proses Reviu Laporan Keuangan Uo Tni Ad Oleh Apip - Belle, Muharram; Sartika , Ika (Jurnal sosial dan sains, 2025)
This research aims to determine the effectiveness of the implementation of the E-Audit System in the financial report review process conducted by the Government Internal Supervisory Apparatus (APIP). This study uses a qualitative method with data from the financial report review at UO TNI AD. ….which defines a business process as "measurable and structured activities to produce certain outputs for specific entities." The objective of the financial report review at UO TNI AD is to assist in the implementation of accounting and the presentation of financial reports for UO TNI AD. The results of this study describe the financial report review influenced by the E-Audit System used, Audit Quality, and APIP that carries out the review process. The benefits of implementing this E-Audit System will reduce examination time, increase accuracy, and have a more comprehensive data range.